As tecnologias na prática docente dos professores de educação física: contribuições do ensino remoto emergencial - Coutinho, Taís Miranda Cardoso (2023)
It is commonly said that contemporary society is computerized and technological and that these resources have opened a path to new possibilities for the production of human life, modifying relationships in different sectors, such as the economy, politics, health and education. In this context, the teacher can face different demands in his classes, putting him in a place of choices. However, teachers need to appropriate theoretical and methodological foundations to materialize strategies that respond to the demands of this digital reality, intensified in the implementation of Emergency Remote Teaching (ERE), during the period of social distancing required by the Covid-19 pandemic. . From this perspective, this research had the general objective: to understand the relationship between Information and Communication Technologies (ICT) and the teaching practice of Physical Education teachers in state public schools in Feira de Santana - Bahia, focusing on Remote Teaching Emergency. In the course of the research, we sought to materialize the following specific objectives: to identify the articulation between Information and Communication Technologies and Education; understand the crossings in the relationship between ICT and Physical Education classes at school and analyze Emergency Remote Teaching in state schools in Feira de Santana in Physical Education classes. This is a descriptive field research with a qualitative approach. With regard to the research participants, it was initially developed with 22 Physical Education teachers from state schools in the municipality of Feira de Santana - Bahia, using the online questionnaire (via Google Forms) as data production instruments, applied , firstly, to teachers to characterize their profile and knowledge of the relationship with ICT. Subsequently, a semi-structured interview was carried out with 2 Physical Education teachers, in order to deepen the understanding of teaching practice and the didactic relationship with ICT in the context of Emergency Remote Teaching, whose analysis was carried out through Discursive Textual Analysis (DTA). The results of the questionnaire showed that the teachers are mostly aged between 30 and 50 years, working in school units located in urban areas, which experienced the teaching of Physical Education content in the ERE. It was evident, for the most part, that Physical Education teachers did not feel prepared for this teaching method, which compromised their teaching practice and resulted in an overload of work and study. Teaching practice in Emergency Remote Teaching was crossed by different determinants such as: lack of operational and pedagogical knowledge about ICT, scarcity of resources and infrastructure, and also by new work configurations and actions by teachers and students.